Modelo experimental de queimadura em pele de rato - Menegat, Tais Amadio [UNIFESP] (2017)
Introduction: In literature, there is a lack of experimental models in reproducible burns to help further research on wound healing. Objective: To develop an experimental model of skin burn on rat skin. Method: This study used 35 male adult Wistar-EPM rats (Rattus norvegicus), whose weight varied from 280g to 380g. All animals were distributed in 3 groups of 10 rats each: the G1 (Group 1) remained immersed in water at 100°C for 3 seconds; the G2 (Group 2) for 5 seconds; and the G3 (Group 3) for 10 seconds. Five animals composed the control group. 24 hours after the scalding, we performed assisted painless death and a histological analysis to assess vascular density and mast cells, to classify injury depth and to conduct a statistical analysis. The presence of ulceration in the burnt area was assessed per group. Results: We analyzed 23 animals after excluding 7 animals for not having presented burn injury due to scalding, despite similar exposure time (4 animals from G1 and 3 from G2). G3 presented greater occurrence of ulceration (80.0%) when compared to G1 (0.0%) and G2 (28.26%). In relation to average number of vessels, G1 and the Control Group presented similar averages, both inferior to G2 and G3. As to mast cells, G2 and G3 presented similar averages, both superior Control Group, proving the degree of burn in each group. Conclusion: The experimental model of scalding burn on rat skin was developed and described the superficial, partial and deep depths of the burns.